1976
DOI: 10.1016/0002-9610(76)90357-3
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid angiography

Abstract: Twelve patients were studied by selective thyroid angiography for the evaluation of solitary thyroid nodule. Under aseptic conditions with local anesthesia a No 7 preshaped catheter was introduced through the femoral artery and guided to the thyrocervical trunk and inferior thyroid artery. Selectively, 2 to 6 cc of the contrast material was injected and a series of radiographs were taken. Striking differences were noticed in vessels in abnormal thyroid gland. In colloid goiter there was no filling of the vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This contrasts sharply with the other methods of absolute blood flow measurement, such as EMF. For some applications, the vascularity indices obtained with radionuclide uptake techniques may yield satisfactory data, although normal vascularity levels have been reported in many patients with toxic uninodular goiter [6], lesions which angiographic studies have described as being highly vascular [12,13]. Woodcock et al [4] have previously reported increased low frequency Doppler-shift signals from such lesions, in contrast to the large high-frequency Doppler shift signals obtained from a follicular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts sharply with the other methods of absolute blood flow measurement, such as EMF. For some applications, the vascularity indices obtained with radionuclide uptake techniques may yield satisfactory data, although normal vascularity levels have been reported in many patients with toxic uninodular goiter [6], lesions which angiographic studies have described as being highly vascular [12,13]. Woodcock et al [4] have previously reported increased low frequency Doppler-shift signals from such lesions, in contrast to the large high-frequency Doppler shift signals obtained from a follicular carcinoma.…”
Section: Discussionmentioning
confidence: 99%